Durability of reinforced concrete from composition to protection selected papers of the 6th International RILEM PhD Workshop held in Delft, the Netherlands, July 4-5, 2013 - International RILEM PhD Workshop Delft, Netherlands) 2013; Andrade, Carmen 1947-; Gulikers, J. (Joost).; Polder, R.; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book presents key advances in the modeling of reinforcement corrosion and concrete durability. It also examines various further aspects of reinforcement corrosion and concrete durability, striking a balance between modeling and testing. Particular attention is paid to innovative treatments for avoiding deterioration, and to methods for modeling performance in a real environment. Some basic aspects related to non-destructive testing techniques are also discussed. Deterioration-related topics addressed in the book include the basis for modeling alkali-silica reactions, chloride diffusion and the development of concrete microstructure; measurement-related topics include cathodic protection, polarization resistance and resistivity. A combined approach using the AFM technique and polarization measurements is examined, and the relation between cracking and corrosion and the treatment of concrete with hydrophobes or innovative products such as hydrotalcite is also discussed.
Visualisation of the Electrical Resistivity Distribution of Reinforced Concrete -- Electronic and Electrolytic Conduction of Cement Pastes with Additions of Carbonaceous Materials -- Influence of Anolyte on Lithium Migration in Concrete -- Durability of Hydrophobic Treatments on Concrete -- Steel Corrosion Rate Measurements in FA Concrete Using Three Electrochemical Techniques -- Cold Drawn Steel Surface Analysis in Contact with Saline Solution: Analysis Using Electrochemical Atomic Force Microscopy -- 25 Years of Experience with Cathodic Protection of Steel in Concrete in the Netherlands -- Corrosion Induced Cracking of Reinforced Concrete -- Influence of Crack Width on Long Term Degradation of Concrete Structures -- Influence of Cracking Caused by Structural Loading on Chloride-Induced Corrosion Process in Reinforced Concrete Elements: A Review -- Effect on Mechanical Properties and Chloride Penetration Resistance of Modified Hydrotalcite in Cement Mortar -- Effects of Nano-silica (NS) Additions on Durability of SCC Mixtures -- The Effect of Climate Change on Freeze-Thaw Cycles in Nordic Climate -- Influence of Environmental Conditions on Pore Structure Change in Mortar with Various Types of Cement -- Study on the Chloride Diffusion Coefficient in Concrete Obtained in Electrically Accelerated Tests -- Towards Structural Modelling of Alkali-Silica Reaction in Concrete -- Free Expansion Tests for ASR at the Level of a Single Aggregate-Matrix Interface: Experimental Results and Numerical Modelling.
Electronic reproduction.
Keywords: Reinforced concrete -- Congresses; Reinforced concrete -- Testing -- Congresses; Electronic books